2012
DOI: 10.1007/s10493-012-9587-0
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of the invasive cattle tick Rhipicephalus microplus, a country-wide survey in Benin

Abstract: The cattle tick Rhipicephalus microplus is currently invading the West African region, and little information is available on the spread of this exotic tick in this region. We set out a country-wide field survey to determine its current distribution in Benin. Ticks were collected on cattle from 106 farms selected by random sampling covering all regions of the country. R. annulatus was found in 70 % of all farms, R. decoloratus was found in 42 %, R. geigyi was found on 58 %, and R. microplus was found on 49 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 14 publications
2
60
0
Order By: Relevance
“…Global economic losses due to ticks and tick-borne diseases have been conservatively put at US$18.7 billion annually (De Clercq et al, 2012). The losses are incurred through the direct effects of ticks as blood sucking parasites and indirect effects as disease vectors which will lead to reduced growth rate, fertility problems, decline in milk production, reduced value of hides and livestock mortalities, notwithstanding the costs associated with treatment and control (Minjauw and Mcleod, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Global economic losses due to ticks and tick-borne diseases have been conservatively put at US$18.7 billion annually (De Clercq et al, 2012). The losses are incurred through the direct effects of ticks as blood sucking parasites and indirect effects as disease vectors which will lead to reduced growth rate, fertility problems, decline in milk production, reduced value of hides and livestock mortalities, notwithstanding the costs associated with treatment and control (Minjauw and Mcleod, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on the relationship that exists between this sub-group of the Rhipicephalus species and results have indicated that Rhipicephalus microplus is displacing other ticks of the same genus in West Africa, South Africa, Tanzania, Mozambique and more recently also in Namibia (De Clercq et al, 2012;De Matos et al, 2009;Lynen et al, 2008;Nyangiwe et al, 2013a;Nyangiwe et al, 2013b). In Zimbabwe, Mason and Norval (1980) reported that the exotic R. microplus was displacing the autochthonous Rhipicephalus decoloratus in the eastern parts of the country with unconfirmed reports suggesting that because of the 1980-1983 drought R. microplus could actually have disappeared from the country (Norval et al, 1992), while subsequent research revealed that R. microplus was still limited to the eastern and northern parts of the country (Katsande et al, 1996) and that it could periodically spread into the interior areas of Zimbabwe (Smeenk et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…on farms around the village where it had first been detected (Madder et al 2011). In 2008, a new focus of invasion was detected in the Department of Mono in south-western Benin, 3 3 West Africa and by 2011 R. microplus had invaded the southern half of that country De Clercq et al 2012). A survey conducted in southern Mozambique, bordering the Kruger National Park in South Africa, in which park only R. decoloratus is present (Horak et al 1992;2003), yielded only R. microplus and no R. decoloratus from cattle and goats sampled at 30 dip-tanks ).…”
Section: Introductionmentioning
confidence: 99%